Platygaster splendidula Ruthe 1859 - Awad, Jessica; Zimmermann, Dominique; Talamas, Elijah (Zenodo, 2024)
Platygaster splendidula Ruthe, 1859 Platygaster splendidulus Ruthe, 1859: 313. Type locality: Iceland. Platygaster hirticornis Förster, 1861: 42. Type locality: Switzerland, Val Roseg. Platygaster lissonotus Förster, 1861: 42. Type locality: Switzerland, Val Roseg. Platygaster lissonota – Dalla Torre 1898: 474 (emendation). — Buhl 1996: 225, figs 13–15. Platygaster splendidula – Dalla Torre 1898: 476 (emendation). Platygaster hirticornis – Buhl 1996: 223, figs 7–9. Material examined Syntypes of Platygaster splendidulus Ruthe ICELAND • 2 specimens; 19 Jun. 1856; [Staudinger leg.]; NHMW-HYM#0005300. Holotype of Platygaster hirticornis Förster SWITZERLAND • 1♂; Rosegg-Thal [Val Roseg];[July1861];[A.Förster leg.]; NHMW-HYM#0005284. Lectotype of Platygaster lissonotus Förster SWITZERLAND • 1 ♂; same data as for holotype; NHMW-HYM#0005282. Paralectotype of Platygaster lissonotus Förster SWITZERLAND • 1 ♂; same data as for holotype; NHMW-HYM#0005283. Published as part of Awad, Jessica, Zimmermann, Dominique & Talamas, Elijah, 2024, A photographic type catalogue of Platygastroidea (Insecta, Hymenoptera) in the Natural History Museum Vienna, pp. 1-58 in European Journal of Taxonomy 938 on pages 10-11, DOI:10.5852/ejt.2024.938.2565, http://zenodo.org/record/12106502